The post-romantic syndrome - Tihanov, Galin (Primerjalna književnost, 2016)
The article presents an original, innovative and interdisciplinary contribution to intellectual history. It examines the intersections between economic and political thought, social philosophy, and aesthetics and literature that inform a pervasive post-romantic discourse on work, wealth and capital spanning the nineteenth century and becoming particularly prominent in the first third of the twentieth century in Germany and Austria.
Keywords: Müller, Adam, 1779-1829; Sombart, Werner, 1863-1941; Jünger, Ernst, 1895-1998; zgodovina diskurzivnih formacij; Romanticism; romantika; postromantika; politična ekonomija; socialna filozofija; skupnost in družba; nemški kulturni prostor